2009
DOI: 10.1038/sj.bjc.6605179
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of 7q34 is specific to juvenile pilocytic astrocytomas and a hallmark of cerebellar and optic pathway tumours

Abstract: BACKGROUND: Juvenile pilocytic astrocytomas (JPA), a subgroup of low-grade astrocytomas (LGA), are common, heterogeneous and poorly understood subset of brain tumours in children. Chromosomal 7q34 duplication leading to fusion genes formed between KIAA1549 and BRAF and subsequent constitutive activation of BRAF was recently identified in a proportion of LGA, and may be involved in their pathogenesis. Our aim was to investigate additional chromosomal unbalances in LGA and whether incidence of 7q34 duplication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
142
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(153 citation statements)
references
References 44 publications
(56 reference statements)
7
142
1
3
Order By: Relevance
“…Previously, we identified tandem duplications or activating mutations (V600E) of the proto-oncogene BRAF at 7q34 as by far the most prevalent genetic mechanism leading to constitutive MAPK pathway activation, occurring in more than 50% of sporadic PAs (4). Subsequent studies confirmed similar or even higher frequencies of BRAF tandem duplications and activating mutations in PAs, with V600E being the most frequent, and showed that the duplication leads to formation of fusion genes of BRAF (5)(6)(7)(8)(9). The unifying molecular feature of all RAF fusion products identified to date is that the RAF kinase domain alone, upon loss of the autoinhibitory N terminus, has the potential to drive proliferation via constitutive MAPK activation.…”
Section: Introductionmentioning
confidence: 56%
“…Previously, we identified tandem duplications or activating mutations (V600E) of the proto-oncogene BRAF at 7q34 as by far the most prevalent genetic mechanism leading to constitutive MAPK pathway activation, occurring in more than 50% of sporadic PAs (4). Subsequent studies confirmed similar or even higher frequencies of BRAF tandem duplications and activating mutations in PAs, with V600E being the most frequent, and showed that the duplication leads to formation of fusion genes of BRAF (5)(6)(7)(8)(9). The unifying molecular feature of all RAF fusion products identified to date is that the RAF kinase domain alone, upon loss of the autoinhibitory N terminus, has the potential to drive proliferation via constitutive MAPK activation.…”
Section: Introductionmentioning
confidence: 56%
“…Later the same year, a comprehensive study by the Collins laboratory showed that this gain is a result of a tandem duplication between BRAF and KIAA1549 (B-K), producing a novel fusion oncogene (11). Several groups have subsequently confirmed the findings and extended the spectrum of RAS-MAPK activation in pediatric gliomas (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 62%
“…To test this hypothesis, we overexpressed BRAF in hTERT-immortalized human astrocytes, as previously published by our group (14), and reversed the hTERT immortalization by telomerase inhibition (ref. 24, Fig.…”
Section: Braf Overexpressing Astrocytes Show Early Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] The biologic significance of BRAF duplication lies in the activation of the MAPK pathway, which can drive tumor proliferation. 9 In addition to KIAA1549:BRAF fusion product, other molecular alterations have been reported in pilocytic astrocytoma, including other BRAF fusion products, 14,15 rare BRAF V600E mutations, 16 BRAF insertions, 17 and KRAS mutations.…”
mentioning
confidence: 99%